Orientation of the snail Biomphalaria straminea (Dunker, 1848) in response to light in a situation of selection - Virginia T. Schall; Pedro Jurberg; Brani Rozemberg (Memorias do Instituto Oswaldo Cruz, 1986)
The behavioral response of Biomphalaria straminea to light was evaluted in terms of location of the snail in a Y-shaped aquarium in a situation of selection and of the rate (cm/hour) and direction of locomotion under homogeneous 9vertical) or differential (horizontal) lighting upon only one arm of the aquarium. The light source consisted of daylight fluorescent lamps with a spectrum close to that of natural light, with illumination varying from 28 to 350 lux. Analysis of the data showed that all animals, whether in groups or isolated, were attracted to light, although the time needed to approach the light source was 50% shorter for the former than for the latter. The rate of locomotion of B. straminea was 35% higher than observed in B. glabrata and 51% higher than that observed in B. tenagophila studied under similar conditions. The results are discussed in terms of social factors and geographical distribution of the three species. As respostas comportamentais de Biomphalaria straminea em relação à luz, foram avaliadas através da localização em um ambiente de escolha em forma de Y e da taxa (cm/hora) e direção da locomoção sob iluminação homogênea (vertical) ou diferencial (horizontal) incidindo em apenas um dos eixos do aparelho. Utilizaram-se como fonte de luz, lâmpadas fluorescentes (luz-do-dia), variando a iluminação de 2,8 a 350 lux. A análise dos dados demonstrou a existência de atração para a luz para os animais em um grupo ou isolados, embora os primeiros com um tempo de aproximação do estímulo 50% inferior aos isolados. A taxa de locomoção de B. straminea foi de 35% superior à encontrada para B. glabrata e 51% superior à de B. tenagophila, espécies estudadas sob condições semelhantes. Os resultados são discutidos quanto a fatores sociais e distribuição geográfica das três espécies.